Textiles and the Making of Sacred Space. (3rd July 2017) - Carroll, Timothy
Abstract : This paper develops a perspective on fabric and its use in religious settings, working from a comparative survey of critical literature arising, primarily, from anthropological writings on cloth and clothing in conjunction with insights gained from ethnographic research among Eastern Orthodox Christians. While the character of Orthodox Christianity and the broad nature of comparative religion shape how the argument is presented, the primary focus of the paper is not on the religious contexts, but rather the particular items of fabric in use, and, more generally, the exact qualities of fabric that allow for its use in such diverse contexts. Rather than taking an argument of historical specificity, the paper is grounded in a material culture approach to fabric, suggesting that a cross-cultural appraisal of fabric that spans different historical periods allows critical insight into the modes of operation within human experience. The central argument of the paper is that, because of the material qualities inherent in fabric, it can be used in such a manner as to make present the sacred.